2022
DOI: 10.1038/s41598-022-10789-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of enhanced aggregation and fibril formation of Parkinson’s disease-related variants of α-synuclein

Abstract: Aggregation of α-synuclein (α-syn) into amyloid fibrils is closely associated with Parkinson’s disease (PD). Familial mutations or posttranslational truncations in α-syn are known as risk factor for PD. Here, we examined the effects of the PD-related A30P or A53T point mutation and C-terminal 123–140 or 104–140 truncation on the aggregating property of α-syn based on the kinetic and thermodynamic analyses. Thioflavin T fluorescence measurements indicated that A53T, Δ123‒140, and Δ104–140 variants aggregated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 94 publications
1
20
0
Order By: Relevance
“…The presence of secondary processes at neutral pH was hinted at by data from Buell et al, and our detailed investigation we has now confirmed that the process is secondary nucleation and not fragmentation [21]. Moreover, several additional studies have reported seed-concentration dependent aggregation kinetics at neutral pH, suggesting that secondary nucleation is a general feature of α-synuclein aggregation [35,36,37,34,38].…”
Section: Discussionsupporting
confidence: 81%
“…The presence of secondary processes at neutral pH was hinted at by data from Buell et al, and our detailed investigation we has now confirmed that the process is secondary nucleation and not fragmentation [21]. Moreover, several additional studies have reported seed-concentration dependent aggregation kinetics at neutral pH, suggesting that secondary nucleation is a general feature of α-synuclein aggregation [35,36,37,34,38].…”
Section: Discussionsupporting
confidence: 81%
“…The proposed strategy, which used optimal and flexible experiment designs based on uncertainty analysis, can provide more flexibility compared to existing approaches such as design of experiments [33], since the exact values of the initial parameters are not fixed and the training features could be parameters which have been calculated based on physical parameters, such as nucleation and growth constants. The nucleation and growth constants were derived from an independent set of experiments carried out in a beaker using the Finke-Watzky (F-W) two-step mechanism [34] which has been applied previously to describe well a wide range of kinetic processes such as protein aggregation [35], [36] and metal nanoparticle formation including silver [37], gold [38], palladium [39] and rhodium [40]. Only one set of chemicals was used in this study providing several pairs of nucleation and growth constants.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, two different approaches were applied. First, we induced amorphous aggregate disassembly while retaining the α-syn fibrils using sample denaturation by low concentrations of guanidinium hydrochloride (GuHCl) 52 . The LLPS and non-LLPS (positive control) condition aggregates were resuspended into a range of GuHCl concentrations (Figure 2A), and the effect of denaturation was monitored by scanning sample optical densities (OD 600 ).…”
Section: Resultsmentioning
confidence: 99%